ANALISIS KINERJA PENYULUH DALAM MEMBERDAYAKAN DAN MEMANDIRIKAN PETANI KELAPA POLA SWADAYA KECAMATAN ENOK KABUPATEN INDRAGIRI HILIR - Oky Berezki; Rosnita Rosnita; Roza Yulida (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This research is aimed by the farmer of coconut knowing the activity of extention worker Smallholder Enok District Inhil Regency. Indragir hilir regency is one of regency in Riau province which the capital is Tembilahan. It is devided into 20 sub districts, 198 villages and 38 district. The area is 329.193 Ha Geografis, Indragiri Hilir Province is located at 00 360 LU until 10 070 LS until 1040 100 BT. This research is conducted Enok sub district Indragiri Hilir from January until February 2016. This research is done with colection sample method, interview and giving quisioner, the total of quisioners is 87. The extention worker in Enok subdistrict must be added in order the area can be devided one extention worker one village, because the extention worker can focus arranging the farmer in the area. The implementation of extention worker is still enough because must be increased to do some activities, especially providing of material is suitable in part of the farmer. The extention worker is conducted in the demonstration and aplication of using course increasing group farmer, quality aspect and quantity aspect. The adviser must increase knowledge in cultivation of coconut, the quality of the farmer is categorized lower because the farmer graduated of SMP and SMA. The adviser conducted is not intensif and maximal especially in part of cultivation of coconut, qonsequently the extention worker must do some trainings who followed by the farmer of cultivation coconut for increasing the knowledge of the farmer and focus what extention worker is done for guiding the farmer of coconut. Keywords: Characterristic, Independent, Performance, Empowerment, Independent